أساليب المعاملة الوالدية وعلاقتها بالتوافق الدراسي لدى تلاميذ المرحلة المتوسطة - دادي عبيدة; حدو أميمة (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة الى الكشف على العلاقة بين اساليب المعاملة الوالدية وعلاقتها بالتوافق الدراسي حيث تمت صياغة الاشكالية العامة على النحو الاتي: هل توجد علاقة بين أساليب المعاملة الوالدية والتوافق الدراسي لدى التلاميذ مرحلة المتوسط؟ وقد شملت عينة الدراسة 100 تلميذ وتلميذة وتم تطبيق المقاييس (مقياس التوافق الدراسي من إعداد يونجمان 1979 ومقياس أساليب المعاملة الوالدية من اعداد مقحوت فتيحة) وقد تم إتباع في معالجة البيانات على منهج وصفي، ثم استخدمنا كل معامل سبيرمان براون، معامل جيتمان، معامل اكرومباخ، معامل الارتباط بيروسون، اختبارات الدلالة الفروق وبعد تطبيق الادوات المستخدمة واستخلاص النتائج تم التوصل الى مايلي: • توجد علاقة ارتباطية ذات دلالة إحصائية بين أساليب معاملة الأب والتوافق الدراسي لدى تلاميذ المرحلة المتوسطة • •توجد علاقة إرتباطية ذات دلالة إحصائية بين المعاملة الأم والتوافق الدراسي لدى تلاميذ المرحلة المتوسطة • •لا توجد فروق دالة إحصائيا في أساليب المعاملة الوالدية (الام والاب) لدى عينة الدراسة تعزى لمتغير الجنس • •لا توجد فروق دالة إحصائيا في التوافق الدراسي لدى عينة الدراسة تعزى لمتغير الجنس. ""The study aimed to investigate the relationship between parenting styles and academic adjustment. The general research question was formulated as follows: Is there a relationship between parenting styles and academic adjustment among middle school students? The study sample included 100 male and female students. Two main instruments were applied: the Academic Adjustment Scale developed by Youngman (1979) and the Parenting Styles Scale developed by Fetiah Maqhout. The data were analyzed using a descriptive method، employing various statistical tools such as the Spearman-Brown coefficient، Guttman coefficient، Cronbach’s alpha، Pearson’s correlation coefficient، and significance tests for differences. After applying the tools and analyzing the results، the study concluded the following: • There is a statistically significant correlation between father’s parenting style and academic adjustment among middle school students. • There is a statistically significant correlation between mother’s parenting style and academic adjustment among middle school students. • There are no statistically significant differences in parenting styles (both maternal and paternal) attributed to the gender variable within the study sample. • There are no statistically significant differences in academic adjustment attributed to the gender variable within the study sample. "
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص علم نفس المدرسي
Keywords: المرحلة المتوسطة; التوافق الدراسي; اساليب المعاملة الوالدية; Parenting styles; academic adjustment; middle school